Analisis Perspektif Mahasiswa Pada Penerapan Kertas Kerja ATLAS (Audit Tool And Linked Archive System) - Sumanto, Agus; Rosdiana, Mega (UMSurabaya Publishing, 2023)
ABSTRACTIn the era of digitalization, auditors must keep up with the times. The